2013
DOI: 10.1186/1471-2407-13-151
|View full text |Cite
|
Sign up to set email alerts
|

p53-independent early and late apoptosis is mediated by ceramide after exposure of tumor cells to photon or carbon ion irradiation

Abstract: BackgroundTo determine whether ceramide is responsible for the induction of p53-independent early or late apoptosis in response to high- and low-Linear-Energy-Transfer (LET) irradiation.MethodsFour cell lines displaying different radiosensitivities and p53-protein status were irradiated with photons or 33.4 or 184 keV/μm carbon ions. The kinetics of ceramide production was quantified by fluorescent microscopy or High-Performance-Liquid-Chromatogaphy and the sequence of events leading to apoptosis by flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Firstly, the cell lines presented a massive G2/M arrest 24 h after photon or carbon ion irradiation. This event was chronologically correlated with the appearance of abnormal nuclei and of micronuclei which is consistent with mitotic catastrophe occurrence [12,14,22]. Moreover, we have shown that ceramide-induced apoptosis 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 Table 2 Kinetics of cell distribution in the cell cycle for the 11 GBM cell lines after a 10 Gy photon or 5 Gy carbon ion irradiation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Firstly, the cell lines presented a massive G2/M arrest 24 h after photon or carbon ion irradiation. This event was chronologically correlated with the appearance of abnormal nuclei and of micronuclei which is consistent with mitotic catastrophe occurrence [12,14,22]. Moreover, we have shown that ceramide-induced apoptosis 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 Table 2 Kinetics of cell distribution in the cell cycle for the 11 GBM cell lines after a 10 Gy photon or 5 Gy carbon ion irradiation.…”
Section: Discussionmentioning
confidence: 82%
“…The kinetics of ceramide release, which is a determining factor in the onset of early and late apoptoses after radiation exposure [14], was analyzed after both types of irradiation. The intracellular production of ceramide was delayed and started only 120 h after photon or carbon ion exposure, regardless of the cell line or its p53 status (Table 4).…”
Section: Induction Of Ceramide Production After Irradiationmentioning
confidence: 99%
“…Countless studies have since validated this initial discovery and indicate that cellular ceramide levels increase early in apoptosis in a variety of cell types and in response to a multitude of apoptotic stimuli including TNFα (Garcia-Ruiz et al 1997; Geilen et al 1997), UV-irradiation (Charruyer et al 2007; Chatterjee and Wu 2001; Deng et al 2002; Siskind et al 2010; Uchida et al 2010; Yao et al 2013), IL3 withdrawal (Siskind et al 2010), ionizing radiation (Alphonse et al 2013; Chmura et al 1997; Deng et al 2008; Haimovitz-Friedman et al 1994; Lu and Wong 2004; Mesicek et al 2010; Moeller et al 2009; Vit and Rosselli 2003), serum withdrawal (Caricchio et al 2002; Fernandez-Ayala et al 2000), etoposide (Chen et al 2006; Lin et al 2005; Perry et al 2000; Sawada et al 2000), staurosporine (Wiesner and Dawson 1996), daunorubicin (Bettaieb et al 1999; Bose et al 1995; Chen et al 2000; Come et al 1999; Jaffrezou et al 1996; Mansat et al 1997), taxol (Charles et al 2001), and cisplatin (Min et al 2007; Noda et al 2001; Siskind et al 2010). Thus, ceramide generation appears to be a common cellular response to apoptosis-inducing agents.…”
Section: Mitochondrial Apoptosismentioning
confidence: 96%
“…Although we identified the cell death pathway following IR through de novo ceramide generation and apoptosis augmented by the inhibition of AC, we have not yet ruled out a contribution of mitotic catastrophe mediated by factors such as caspase-2. This mechanism of IR-induced cell damage/death is of great interest to us, as ceramide may be of importance to this process (73).…”
Section: Discussionmentioning
confidence: 99%